Factors and Costs Associated With Delay in Treatment Initiation and Prolonged Length of Stay With Inpatient EPOCH Chemotherapy in Patients With Hematologic Malignancies. (16th March 2017) - Accordino, Melissa K.; Wright, Jason D.; Vasan, Sowmya; Neugut, Alfred I.; Hillyer, Grace C.; Hershman, Dawn L.
ABSTRACT: Reducing delays related to inpatient chemotherapy may reduce healthcare costs. Using a national database, we identified patients with lymphoma/leukemia with ≥1 etoposide, vincristine, doxorubicin, cyclophosphamide, and prednisone (EPOCH) chemotherapy claim and evaluated chemotherapy initiation delay (ID), >1 day from admission. Standard tests/procedures prior to initiation were evaluated. Among 4453 inpatient cycles, 19.7% had ID, odds ratio 2.28 (95% confidence interval: 1.83–2.85) with cycle 1 compared to cycle 2, and mean costs were higher in patients with ID than without ID ( p < .0001). Prior to cycle 1, patients were more likely to undergo routine diagnostic procedures compared to subsequent cycles. Efforts to perform routine procedures prior to admission may reduce hospital length of stay and costs.